The gut of geographically disparate Ciona intestinalis harbors a core microbiota. - Larry J Dishaw; Jaime Flores-Torres; Simon Lax; Kristina Gemayel; Brittany Leigh; Daniela Melillo; M Gail Mueller; Lenina Natale; Ivana Zucchetti; Rosaria De Santis; Maria Rosaria Pinto; Gary W Litman; et al. (PLoS ONE)
It is now widely understood that all animals engage in complex interactions with bacteria (or microbes) throughout their various life stages. This ancient exchange can involve cooperation and has resulted in a wide range of evolved host-microbial interdependencies, including those observed in the gut. Ciona intestinalis, a filter-feeding basal chordate and classic developmental model that can be experimentally manipulated, is being employed to help define these relationships. Ciona larvae are first exposed internally to microbes upon the initiation of feeding in metamorphosed individuals; however, whether or not these microbes subsequently colonize the gut and whether or not Ciona forms relationships with specific bacteria in the gut remains unknown. In this report, we show that the Ciona gut not only is colonized by a complex community of bacteria, but also that samples from three geographically isolated populations reveal striking similarity in abundant operational taxonomic units (OTUs) consistent with the selection of a core community by the gut ecosystem.